Perancangan Modul Interaktif pada Mata PelajaranSimulasi dan Komunikasi Digital Siswa SMK Kelas X - Veny Asman; M Menrisal; Rahmatul Husna Arsyah (Universitas Putra Indonesia YPTK Padang, 2020)
This study aims to create an interactive module that meets the requirements Valid, Practical and effective for simulation and digital communication subjects. This research is a Research and Development research conducted at SMK. The test subjects in this study were students of class X SMK Negeri 1 Padang. The results of the assessment of the three validators as a whole were 82.72% so that the validity level could be interpreted as valid. The overall assessment of practicality is 90.51%, so that the level of practicality can be interpreted to be very practical to use, as well as an assessment of the effectiveness of 89.67%, so that thelevel of effectiveness can be interpreted well